Synthesizing Islam with Local Values: The Philosophy of Minangkabau Speech Kato nan Ampek and the Qur’an - Rezi, Muhamad; Raya, Ahmad Thib; Hariyadi, Muhammad; Ibrahim , Mohamed Akhiruddin; Kirin, Arwansyah (RUSYDIAH: Jurnal Pemikiran Islam, 2025)
This article examines the possibility of synthesizing substantively two different components, namely the Qur'an and the local wisdom of Nusantara, Indonesia. In this case, Kato nan Ampek is a philosophy of speech acts in Minangkabau. There are four Kato: Mandaki, Manurun, Malereng, and Mandata. Each of the Kato nan Ampek is used according to the speech partner. This research was conducted qualitatively with a synthesis approach. It was found that Kato Mandaki, in substance and use, is by the principles of Qawlan Karîma; Kato Manurun, in substance, can be synthesized with Qawlan Sadîda, and the principle of the practice of Kato Manurun should be based on the principle of Qawlan Sadîda; and with Kato Malereng, in practice, it should also be based on the principle of Qawlan Balîgha; as well as Kato Manurun, its use should also be based on the principle of Qawlan Layyina.